Processing Rubber Sandal Waste into Paving Blocks in Mulyaharja Village, Bogor City - Ratnawati, Beata; Prasetya, Dimas Ardi; Tunggadewi, Andini Tribuana; Budiharto, Ivone Wulandari; Sayekti, Ayutyas; Hidiya, Miesriany; Suri, Wiranda Intan; Meliana, Linda; Natalia, Adelisa; Ramadhani, Mulia Ilmi (Universitas Syiah Kuala, 2024)
The accumulation of non-biodegradable rubber sandal waste poses significant environmental and aesthetic challenges, with the risk of pollution. Processing rubber sandal waste is needed to reduce the potential for environmental pollution. This study aims to convert sandal waste into paving blocks in the form of community activity programs. The program begins with a needs survey and resource analysis, followed by community training in paving block production techniques using rubber sandal waste. Direct assistance is provided during the initial production phase to ensure the quality of products meets the required standards. Promotion and marketing efforts further raise public awareness of eco-friendly products, opening new business opportunities. This program fosters synergy between local communities, academia, and industry in sustainable waste management, creating new economic value and supporting environmental preservation. Periodic evaluations reveal the program's success in enhancing community awareness and skills in waste management, making it a potential model for other areas facing similar issues. The technology is versatile, applicable across various locations, including residential settings, allowing for effective waste utilization and reduced environmental pollution.